Inside the Kaisha : - Yoshimura, Noboru (Harvard Business School Press, 1997)
The book is organized around six puzzles about Japanese business behavior that perplex outsiders. The authors unravel each puzzle in a systematic way to demonstrate why, from the Japanese perspective, the behavior is in fact appropriate and consistent. For each puzzle, the authors generate a set of specific insights that can be used in everyday business practice.